2021
DOI: 10.3390/s22010211
|View full text |Cite
|
Sign up to set email alerts
|

Force Myography-Based Human Robot Interactions via Deep Domain Adaptation and Generalization

Abstract: Estimating applied force using force myography (FMG) technique can be effective in human-robot interactions (HRI) using data-driven models. A model predicts well when adequate training and evaluation are observed in same session, which is sometimes time consuming and impractical. In real scenarios, a pretrained transfer learning model predicting forces quickly once fine-tuned to target distribution would be a favorable choice and hence needs to be examined. Therefore, in this study a unified supervised FMG-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In the literature, CNN based GAN models are more dominant and have shown good performances in image classifications and pattern recognition. In our previous studies, we found that the model could effectively learn discriminative features of time-series interactive data [16], [17]. In this study, window size of the FMG-DCGAN model was set to 10ms evaluate the smallest time-series input (every single row) in the system.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, CNN based GAN models are more dominant and have shown good performances in image classifications and pattern recognition. In our previous studies, we found that the model could effectively learn discriminative features of time-series interactive data [16], [17]. In this study, window size of the FMG-DCGAN model was set to 10ms evaluate the smallest time-series input (every single row) in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Common industrial tasks such as object transportation or handover may require the worker to apply hand forces during interactions with the robot. Estimating the applied hand force to interact with a robot in dynamic motions using FMG signals was found favorable in physical interactions [ 48 , 49 , 50 , 51 , 52 , 53 ]. These studies implemented compliant collaboration, where a robot’s trajectory was dictated by the applied hand force of a human worker.…”
Section: Introductionmentioning
confidence: 99%
“…In recent sEMG-based human-robot interactions (HRI) studies, deep learning techniques such as convolutional neural networks (CNN) and long-term short memory (LSTM) were used for dynamic or static force estimations [7][8][9]. A few studies were conducted recently where FMG bio-signals were used for applied force estimations during physical human-robot interaction (pHRI) activities [10][11][12]. In [10], pHRI between several participants and a fixed linear robot was investigated using intra-session data.…”
Section: Introductionmentioning
confidence: 99%
“…Such an individual-specific, intra-session biased model predicted interactive forces (94%>R 2 >82%) in real-time during the same session. Interestingly, pHRI with inter-session FMG data using domain adaptation and generalization in a planar workspace was recently investigated with improved force estimations [11,12]. In these 2D-pHRI studies, a generalized model trained with long-term FMG distributions (collected over a period) predicted unseen target data during repetitive usage or during interactions with a new participant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation